Comparison of the Efficacy of Nonsteroidal Anti-Inflammatory Drugs and Opioids in the Treatment of Acute Renal Colic: A Systematic Review and Meta-Analysis - Leng, Xie-Yuan; Liu, Chang-Ning; Wang, Shi-Chan; Peng, Hao-Dong; Wang, De-Guang; Pan, Hai-Feng (Frontiers in Pharmacology, 2022)
Background: Although multiple randomized controlled trials (RCTs) and systematic review and meta-analysis were performed to investigate the efficiency and safety of nonsteroidal anti-inflammatory drugs (NSAIDs) and opioids in the treatment of acute renal colic, the therapeutic regimen of renal colic is still controversial. Therefore, the aim of this study was to derive a more concise comparison of the effectiveness and safety between NSAIDs and opioids in the treatment for patients with acute renal colic by a systematic review and meta-analysis. Design: We searched PubMed, Embase, and Cochrane Central Register of controlled trials for seeking eligible studies. The pooled mean difference (MD) or risk ratio (RR) with 95% confidence interval (CI) was calculated using the random effects model. The primary outcome was assessed according to the Grading of Recommendations Assessment, Development and Evaluation. Results: A total of 18 studies involving 3,121 participants were included in the systematic review and meta-analysis. No significant difference between the NSAID and opioid groups was observed, with changes in the visual analog scale (VAS) at 0–30 min (MD = 0.79, 95% CI: −0.51, 2.10). NSAIDs in the form of intravenous administration (IV) had no better effect on the changes in the VAS at 0–30 min, when compared to opioids (MD = 1.25, 95% Cl: −4.81, 7.3). The NSAIDs group in the form of IV had no better outcome compared to the opioids group, as well as the VAS at 30 min (MD = −1.18, 95% Cl: −3.82, 1.45; MD = −2.3, 95% Cl: −5.02, 0.42, respectively). Moreover, similar results of this outcome were also seen with the VAS at 45 min (MD = −1.36, 95% Cl: −5.24, 2.52). Besides, there was a statistical difference in the incidence of later rescue (RR = 0.76, 95% CI: 0.66, 0.89), drug-related adverse events (RR = 0.44, 95% CI: 0.27, 0.71), and vomiting (RR = 0.68, 95% CI: 0.49, 0.96). Conclusion: There is no significant difference between the NSAIDs and opioids in the treatment of renal colic in many outcomes (e.g., the VAS over different periods using different injection methods at 30 and 60 min), which has been focused on in this study. However, the patients who were treated using NSAIDs by clinicians can benefit from fewer side effects.